Determinants of Purchase Intention for Halal Skincare Products Among Generation Z Consumers - Dian Amanda Putri; Edwin Zusrony; Myra Andriana (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to analyze the influence of halal awareness, BPOM labels, and e-WOM on the interest in purchasing skincare products on e-commerce among Generation Z. Methodology: This study employed a quantitative approach with multiple linear regression analysis. Data were obtained through a questionnaire distributed to Generation Z in Semarang Regency who were interested in purchasing skincare products through e-commerce. Results: The results of the study showed that all independent variables, namely: halal awareness, BPOM label and e-WOM had a positive and significant impact on purchase intention (P-Value < 0.05). Findings: Based on the F test, the results of the halal awareness, BPOM label, and e-WOM variables simultaneously impacted the purchase intention of skincare products among Gen Z in Semarang Regency with a P-Value of 0.000. Novelty: The insights generated through this research approach have not been widely explored previously in the literature, particularly in the context of young religious consumers. This geographic focus on Semarang Regency may help provide important contextual contributions. Originality: This study provides new insights by showing that spiritual leadership does not contribute to OCB, in contrast to job satisfaction, as well as highlighting the role of spirituality as a mediator which has not been extensively studied before. Conclusion: The study concluded that to increase interest in purchasing skincare products among Gen Z, the main focus should be on increasing halal awareness, BPOM labels, and e-WOM. Type of Paper: Empirical research type.